Rhinovirus upregulates transient receptor potential channels in a human neuronal cell line: implications for respiratory virus-induced cough reflex sensitivity. Issue 1 (3rd September 2013) - Abdullah, H; Heaney, L G; Cosby, S L; McGarvey, L P A
Abstract : Background: The mechanism underlying respiratory virus-induced cough hypersensitivity is unknown. Upregulation of airway neuronal receptors responsible for sensing physical and chemical stimuli is one possibility, and the transient receptor potential (TRP) channel family are potential candidates. We have used an in vitro model of sensory neurons and human rhinovirus (HRV-16) to study the effect of virus infection on TRP expression. Methods: IMR-32 neuroblastoma cells were differentiated in culture to express three TRP channels: TRPV1, TRPA1 and TRPM8. Flow cytometry and qRT-PCR were used to measure TRP channel protein and mRNA levels following inoculation with live virus, inactivated virus, virus-induced soluble factors or pelleted virus particles. Multiplex bioassay was used to determine nerve growth factor (NGF), interleukin (IL)-1β, IL-6 and IL-8 levels in response to infection. Results: Early upregulation of TRPA1 and TRPV1 expression occurred 2–4 h post infection. This was independent of replicating virus as virus-induced soluble factors alone were sufficient to increase channel expression 50-fold and 15-fold, respectively. NGF, IL-6 and IL-8 levels, increased in infected cell supernatants, represent possible candidates. In contrast, TRPM8 expression was maximal at 48 h (9.6-fold) and required virus replication rather than soluble factors. Conclusions: We show for the first time that rhinovirus can infect neuronal cells. Furthermore, infection causes upregulation of TRP channels by channel-specific mechanisms. The increase in TRPA1 and TRPV1 levels can be mediated by soluble factors induced by infection whereas TRPM8 requires replicating virus. TRP channels may be novel therapeutic targets for controlling virus-induced cough.